Reliability and validity of finger strength and endurance measurements in rock climbing - Lubomirov Michailov, M.; Baláš, J.; Kolev Tanev, S.; Stoyanov Andonov, H.; Kodejška, J.; Brown, L. (Research Quarterly for Exercise and Sport, 2018)
Purpose: An advanced system for the assessment of climbing-specific performance was developed and used to: (a) investigate the effect of arm fixation (AF) on construct validity evidence and reliability of climbing-specific finger-strength measurement; (b) assess reliability of finger-strength and endurance measurements; and (c) evaluate the relationship between finger flexor all-out test scores and climbing ability. Methods: To determine the effect of AF, 22 male climbers performed 2 maximal strength and all-out tests with AF (shoulder and elbow flexed at 90°) and without AF (shoulder flexed at 180° and elbow fully extended). To determine reliability, 9 male climbers completed 2 maximal strength tests with and without AF and an all-out and intermittent test without AF. Results: The maximal strength test without AF more strongly determined climbing ability than the test with AF (r2 = .48 and r2 = .42 for sport climbing; r2 = .66 and r2 = .42 for bouldering, respectively). Force and time variables were highly reliable; the rate of force development and fatigue index had moderate and low reliability. The maximal strength test with AF provided slightly higher reliability than without AF (intraclass correlation coefficient [ICC] = 0.94, ICC = 0.88, respectively). However, smaller maximal forces were achieved during AF (484 ± 112 N) than without AF (546 ± 132 N). All-out test average force had sufficiently high reliability (ICC = 0.92) and a relationship to sport climbing (r2 = .42) and bouldering ability (r2 = .58). Conclusion: Finger strength and endurance measurements provided sufficient construct validity evidence and high reliability for time and force parameters. Arm fixation provides more reliable results; however, the position without AF is recommended as it is more related to climbing ability.